1994
DOI: 10.1111/j.1365-2672.1994.tb03063.x
|View full text |Cite
|
Sign up to set email alerts
|

Variations in concentrations of bacterial metabolites, enzyme activities, moisture, pH and bacterial composition between and within individuals in faeces of seven healthy adults

Abstract: Variations between and within individuals, and correlations between concentrations of bacterial metabolites, including putrefactive products, ammonia and short chain fatty acids (SCFAs), enzyme activities, moisture and pH, as well as bacterial composition, were studied in faecal samples from seven healthy adults over a period of 7 months. Large variations, both between and within individuals, were observed in concentrations of putrefactive products. Although values for ammonia, SCFAs, enzyme activities, moistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
32
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 44 publications
7
32
2
Order By: Relevance
“…The greater stability of the numerically predominant anaerobe populations (clostridia, bifidobacteria, and bacteroides) compared to the facultative anaerobes is in agreement with the results of other authors (8,25,26). The most striking difference between the present and previously published results are the consistently low bacteroides counts.…”
Section: Discussioncontrasting
confidence: 44%
“…The greater stability of the numerically predominant anaerobe populations (clostridia, bifidobacteria, and bacteroides) compared to the facultative anaerobes is in agreement with the results of other authors (8,25,26). The most striking difference between the present and previously published results are the consistently low bacteroides counts.…”
Section: Discussioncontrasting
confidence: 44%
“…Our results are in basic agreement with those of a previous study (10) in respect of the relationships among fecal pH, water content, SCFAs concentration and concentrations of intestinal putrefactive products. On the other hand, we did not find any significant changes in the amount of CO 2 and indicators of intestinal environment in response to dietary manipulation.…”
Section: Discussionsupporting
confidence: 92%
“…This finding strongly supports the suggestion that the composition of the microbiota plays an important role in human health. Inter-and intraindividual variations in bacterial composition, enzyme activities, moisture, and pH in healthy individuals have been previously demonstrated, regardless of DAG production (23). Moreover, variations in fecal DAG content have been demonstrated in vivo, and it has been suggested that this is due to changes in the proportion of bacterial species possessing phospholipase C, an enzyme involved in DAG conversion (31).…”
Section: Discussionmentioning
confidence: 99%